Social Identity, Boundary Breaking, and Ritual: Saul's Recruitment on the Road to Damascus - Lamoreaux, Jason T. (Biblical theology bulletin, 2008)
Within the context of collectivist cultures, moving from one group to another, or changing identities, is an arduous and sometimes violent task. Saul's move from zealous Judean to follower of Jesus is depicted as a violent time of separation and aggregation. In this study, I use the anthropology of Ritual and Social Identity to construct a model of Social Identity and Boundary Breaking Ritual so that modern interpreters can better understand what is happening to Saul on the road to Damascus. Furthermore, utilizing terminology from the study of New Religious Movements, I argue that “recruitment” be used as a more accurate term than “conversion” in this context. I also compare the passage to other similar passages found in the literature of the Greco-Roman world. The models and comparisons provide a methodological framework to help modern interpreters better avoid anachronistic readings of Acts 9:1-19a.